Pengembangan Materi ‘Ubudiyah Berbasis Teknologi Majelis Ta’lim Ruhul Islam Kecamatan Barumun Kabupaten Padang Lawas - Mhd. Hasbin Daulay; Erawadi Erawadi; Abdusima Nasution (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2025)
Islamic Religious Education (IRE) learning at Majelis Taklim Ruhul Islam in Barumun is still dominated by lecture methods and textbook usage, making it less engaging and less effective in enhancing participants’ understanding—especially of worship-related material that is both conceptual and practical. Low participant involvement and the limited use of educational technology present major challenges, particularly for digital native learners who are more interested in interactive media. This study aims to develop a Quizizz-based digital learning media for worship material in IRE at SMK Negeri 1 Barumun, and to examine its validity, practicality, and effectiveness. The research employed the ADDIE development model with IRE teachers and tenth-grade students as subjects. Data were collected through observation, interviews, questionnaires, tests, and expert validation. Results showed the media’s validity at 95.48% (highly valid), practicality at 95.50% (teachers) and 82.45% (students), and effectiveness with an N-Gain of 63.96 (moderate category). The media effectively improves understanding and participation, and aligns with the principles of the Merdeka Curriculum.